Silicosis in sandblasters: a case study adapted for use in U.S. high schools - USA. National Institute for Occupational Safety and Health (Cincinnati, 2002)
To learn about epidemiology by studying an occupational hazard, a disease associated with the hazard, and the methods for preventing the disease. Epidemiology is the study of why and how a disease occurs and spreads in populations. The purpose of epidemiology is to prevent and control disease by identifying its causes and the methods for control. Occupational epidemiology is the study of disease or injury related to work activities and the worksite. More than 2 million U.S. workers are potentially exposed to dusts containing crystalline silica. Prolonged inhalation of silica-containing dusts puts these workers at risk for the disease silicosis—a nodular fibrosis of the lungs that causes shortness of breath. More than 100,000 U.S. workers are in high-risk occupations such as sandblasting. Most sandblasters work in construction and shipbuilding. Workers may be exposed to crystalline silica in many other industries, including surface and underground mining, pottery, drywall hanging, glassmaking, foundry work, quarry work, work with sandblasting materials, agriculture, and automotive repair.